Communication and Peace: Interview with Olga Rodríguez San Francisco - Peña Ascacíbar, Gonzalo (CIC. Cuadernos de Información y Comunicación, 2023)
Interview with the journalist and specialist in information on international conflicts Olga Rodríguez Francisco, graduate in Journalism at Complutense University. She is a writer,  an expert and author committed to in-depth coverage of conflicts in areas of the Middle East, particularly related to Human Rights , Freedom of information and Press and respect for peoples and minorities in post-colonial and militarized world.
Keywords: Olga Rodríguez; international journalism; Middle East; human rights; conflict and communication; activism; press freedom